144. MSG-15: Pharmacokinetic (PK), Adverse Events (AEs), and Tolerability Data from an Open Label Randomized Clinical Trial (RCT) Comparing Oral Suba-itraconazole (SUBA-ITC) to Conventional Itraconazole (C-ITC) for Treatment of Endemic Mycosis (EM). (31st December 2020) - Pappas, Peter G; Spec, Andrej; Miceli, Marisa H; Proia, Laurie; Arauz, Ana Belen; Hayes, Justin; Peinhardt, Alisa; McMullen, Rachel; Moore, Mary K; McGwin, Gerald; Thompson III, George R
Abstract: Background: C-ITC is a drug of choice for non-life-threatening, non-CNS histoplasmosis, blastomycosis, sporotrichosis, coccidioidomycosis and other EM. Oral C-ITC is problematic due to inconsistent absorption often leading to sub-therapeutic serum levels. SUBA-ITC is an FDA approved formulation which utilizes nanotechnology to provide more consistent absorption when compared to C-ITC. We performed an open-label RCT comparing SUBA-ITC to C-ITC for non-life-threatening non-CNS EM, and is the first US based RCT examining SUBA-ITC. Herein we report the PK during the first 6 wks of study therapy (rx) and drug-related AEs and tolerability throughout the course of rx. Methods: Subjects with a proven or probable EM, who had received < 14 days prior antifungal tx, and were able to take po meds were eligible. Those with life-threatening and CNS disease or prohibited meds were excluded. Subjects were randomized to SUBA-ITC 130 mg or C-ITC 200mg, both PO BID, for up to 6 mo. All subjects received loading doses x 3d. Clinical assessment was performed on d 7, 14, 28, 42, 84, and 180. PK and safety evaluations were performed on d 7, 14 and 42. Serum levels and AUC were calculated and demonstrated using combined ITC and hydroxy-ITC measurements. Tolerability was based on subject ability to remain on rx. Results: 62 subjects are included in this analysis (31 each in SUBA-ITC and C-ITC, respectively). Median serum levels of ITC + hydroxy-ITC at d 7, 14 and 42 were consistently higher in the SUBA-ITC arm (Fig 1, p=0.8, NS). Combined AUC (ITC+hydroxy-ITC) were 2951 and 2845 for SUBA-ITC and C-ITC, respectively (NS). 4 subjects in each arm had sub-therapeutic d 7 levels (< 1000ng/ml). Drug-related AEs and tolerability were similar in both arms (Table 1). Lower extremity edema, hypertension, nausea, and anorexia were the most common AEs. Premature study withdrawal was seen in 12 (19%) subjects overall (5 and 7 subjects, respectively on SUBA-ITC and C-ITC). Figure 1 Conclusion: SUBA-ITC dosed at 130 mg BID PO is safe, well-tolerated, and consistently leads to combined serum ITC/hydroxy-ITC levels and AUC that are higher (NS) when compared to C-ITC 200 mg BID. Moreover, compared to C-ITC, SUBA-ITC achieves these serum levels when administered at substantially lower daily doses (130mg BID vs 200 mg BID). Disclosures: Peter G. Pappas, MD, Mayne Pharma (Scientific Research Study Investigator) Andrej Spec, MD, MSCI, Mayne (Consultant, Grant/Research Support) Marisa H. Miceli, MD, FIDSA, SCYNEXIS, Inc. (Advisor or Review Panel member) Laurie Proia, MD, Mayne Pharma (Scientific Research Study Investigator) Ana Belen Arauz, MD, Mayne Pharma (Scientific Research Study Investigator) Justin Hayes, MD, Mayne Pharma (Grant/Research Support) Alisa Peinhardt, MAIS, BSN, Mycoses Study Group Education and Research Consortium (Consultant)